Checklist of the Cistus L. hybrids occurring in Southern Portugal - Schwarzer, Udo; Schwarzer, Claudia (Mediterranean Botany, 2025)
Southwest Portugal is rich in Cistus species and its hybrids. A global review of all sixteen Cistus nothotaxa found in Southern Portugal is provided with a nomenclatural update and the typification of previous described nothotaxa (Cistus × daveauanus). A new hybrid is described (C. × aljezurensis nothosp. nov.) relating the introgression between, C. crispus and C. inflatus.
Keywords: Cistaceae; hybridization; nothospecies; Aljezur; Algarve; Portugal